2014
DOI: 10.1021/ja5098379
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Enzymatic and Organic Electrocatalytic Cascade for the Complete Oxidation of Glycerol

Abstract: We demonstrate the complete electrochemical oxidation of the biofuel glycerol to CO2 using a hybrid enzymatic and small-molecule catalytic system. Combining an enzyme, oxalate oxidase, and an organic oxidation catalyst, 4-amino-TEMPO, we are able to electrochemically oxidize glycerol at a carbon electrode, while collecting up to as many as 16 electrons per molecule of fuel. Additionally, we investigate the anomalous electrocatalytic properties that allow 4-amino-TEMPO to be active under the acidic conditions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 32 publications
1
107
1
8
Order By: Relevance
“…Recent progress for example in multi-catalyst "cascade" catalytic systems offers new promise for better performance in complex multi-electron reactions such as glycerol oxidation [6]. New and better catalyst systems are still desirable and in particular metal-free and enzymeless processes based on molecular organo-catalysts are attractive [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress for example in multi-catalyst "cascade" catalytic systems offers new promise for better performance in complex multi-electron reactions such as glycerol oxidation [6]. New and better catalyst systems are still desirable and in particular metal-free and enzymeless processes based on molecular organo-catalysts are attractive [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyl group oxidation is a fundamentally important reaction with a broad range of applications in synthetic bio-transformations [7][8][9] and radical initiated polymerisation reactions [10], in sensors [11] and in complex catalyst systems for biofuel cells [12]. It is of interest to develop modified substrates with TEMPO Electronic supplementary material The online version of this article (doi:10.1007/s12678-015-0284-8) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…The TEMPOcatalysed oxidation of primary alcohol groups proceeds via overall two-electron oxidation of the alcohol requiring two equivalents of TEMPO + . Most studies have reported that TEMPO exhibits good selectivity towards primary alcohol oxidations in alkaline conditions (to aldehydes or to carboxylates [17,18]), but there are also more complex examples of secondary alcohols being oxidised to ketones [19] and examples of novel multi-catalyst multi-step oxidations [12].…”
Section: Introductionmentioning
confidence: 99%
“…A low activity is observed at acidic pH, because below the pKa of hydroxylamine, the coupled deprotonation/ oxidation is no longer facilitated. 14 However, the oxidation signal remains significant above pH 4, demonstrating that TEMPO could work with H 2 O 2 -producing oxidases that operate in acidic pH ranges.…”
Section: Resultsmentioning
confidence: 99%